MODERN PHOTOBOOK AS A DESIGN OBJECT: SYSTEMATIZATION BY WAY of SUBMITTING CONTENT - Сафронова, А. В.; Михайлова, Р. Д. (Art and Design, 2020)
To explore the features and characteristics of a modern photobook as an object of design, its artistic and compositional solutions, types of content presentation; identify the state, trends in the development of photobooks of relevant types in the world and in Ukraine. The article uses visual-analytical analysis to process samples and written sources, typological – to identify criteria for the distribution of samples and their systematization, comparative – for stylistic, compositional, content, analysis of various works of photography, photo albums and other publications. Based on the analysis of scientific sources, modern foreign and Ukrainian photobooks, it is generalized the approaches to its artistic and compositional solutions and design, the classification of types of photo books by the way of presenting content as specific publications, the grounds for combining photos in a series is made, which include : common theme; common idea; common plot; common formalities; community of associations. The characteristics of the photo book as an object of design are formed: the features of artistic and compositional design solutions of a number of Ukrainian photobooks, which have been recognized as works of photography, are systematized; the leading tendencies of development of concrete types of photo books in the way of presenting content in Ukraine are revealed. On the basis of art analysis of photobooks by the way of presenting content, trends in its development within modern photography, features of design of a number of photographic works, which over time have acquired high artistic and market value or received recognition at international competitions are revealed. Characteristic features of photo reproduction are determined, which give Ukrainian photo books a distinct national character.